Robotic Arm 6 Degree of Freedom (DoF) on SCADA-based Modular Production System (MPS) - Sihono; Suryono; Bangun Krishna; Sri Kusumastuti; Bagus Yunanto; Fadlil Maulana; Heksa Tiara Sasti (Nusantara Science and Technology Proceedings, 2022)
Technology was created to help humans in completing the job. Technological developments are very rapid and affect various fields of life, one of which is the industrial sector. The development of technology in the industrial sector can be seen from robotics to perfect resources to run effectively and efficiently. Among the robots that are often used in the industrial world are arm robots. Robotic arms can do continuous work. The advantage of robot arms is producing a more precise quality of work that is done repeatedly and can be reprogrammed for several different tasks. The existence of a robot arm is beneficial to speed up the work process with maximum results in the industrial world. However, the previously developed robot arm is less than 6 DoF, so the movement is still not accessible. This research implements a Robotic Arm 6 Degree of Freedom (DoF) on SCADA-based Modular Production System (MPS) from these problems. The task of the robot arm is to move the material from one place to another place. One cycle task can be finished in 55 seconds with a speed of 100%, and if the speed is 50%, it takes 90 seconds. The data above can measure the effectiveness of the maneuver robot for taking the task. When the robot arm works and is suddenly blocked by a foreign object that makes the robot arm stops moving, the robot arm automatically turns off, and an overload warning appears on the pendant.